Methodological and Statistical Considerations for the National Children's Study - Hays, Ron D.; Hubble, David; Jenkins, Frank; Fraser, Alexa; Carew, Beryl (Frontiers in Pediatrics, 2021)
The National Children’s Study (NCS) statistics and item response theory group was tasked with promoting the quality of study measures and analysis. This paper provided an overview of six measurement and statistical considerations for the NCS: 1) Conceptual and Measurement Model; 2) Reliability; 3) Validity; 4) Measurement Invariance; 5) Interpretability of Scores; and 6) Burden of administration. The guidance was based primarily on recommendations of the International Society of Quality of Life Research.